Efficacy and safety of small molecule drugs in the treatment of pityriasis rubra pilaris—A systematic review - Zhang, Xiaofang; Wei, Kebo; Song, Hongxia; Chen, Xi; Yang, Jiao; Zhao, Jianmei; Jiang, Yugu; He, Xin (Frontiers in Medicine, 2025)
BackgroundPityriasis rubra pilaris is a chronic, scaly, keratotic skin disease, mainly manifested as scaly plaques and keratinized hair follicles. This condition significantly impacts the patient’s quality of life and is considered one of the intractable diseases in dermatology. Currently, no satisfactory clinical treatment options are available for this condition, presenting a considerable challenge for dermatologists. We conducted this systematic evaluation to assess the therapeutic potential of existing small molecule drugs for this disease.ObjectivesTo conduct a systematic review of the existing literature on the use of small molecule drugs for treating pityriasis rubra pilaris and to evaluate their clinical effectiveness and safety.MethodsWe conducted a systematic review of all the literature on small molecule drugs for the treatment of Pityriasis rubra pilaris and searched several databases until November 2024, including PubMed, Embase, Web of Science, and the Cochrane Library.ResultsA total of 16 patients with pityriasis rubra pilaris from 11 publications were included. The small molecule drugs, including apremilast, upadacitinib, abrocitinib, and tofacitinib, demonstrate good efficacy and safety in the treatment of pityriasis rubra pilaris across all ages, particularly in patients who have failed systemic therapy and have a poor response to biological agents. However, the conclusions are limited by the small sample size and need to be further confirmed through large-scale randomized controlled clinical trials.ConclusionSmall molecule drugs demonstrate favorable clinical efficacy and safety in the treatment of refractory pityriasis rubra pilaris, exhibiting a relatively rapid onset and a high safety profile. However, the findings in the literature may be affected by publication bias.